Group schema therapy for patients with cluster‐C personality disorders: A case study on avoidant personality disorder. Issue 5 (4th February 2021) - Bachrach, Nathan; Arntz, Arnoud
Abstract: This article presents a clinical illustration of group schema therapy (GST) for cluster‐C personality disorders (CL‐C PDs) to provide therapists an example on how one can perform GST for CL‐C PDs and break through persistent avoidance and control mechanisms. A summary of evidence supporting the effectiveness of GST for CL‐C PD's is given followed by an overview of basic principles of schema therapy and GST. A case presentation next illustrates the application of GST principles and interventions in the GST CL‐C protocol, which improve clients understanding of emotional core needs and development of adaptive ways of getting needs better met, instead of avoiding life. Implications of the case for future applications of GST for CL‐C PDs are discussed.